NeoLiberal Scotland: Class and Society in a Stateless Nation. - Patricia McCafferty, David Miller and Neil Davidson (Cambridge Scholars Pub., 2010)
Each of the book's contributors is engaged in critical academic research across a broad spectrum in Scotland. Although they are specialists in their chosen fields, they share a concern to problematise the post-devolution, 'new' Scotland by discussing it fully and effectively in the neo-liberal context of the 21st century. In addition, all of the authors are activists in the anti-capitalist, environmental, socialist and anti-war movements and are therefore engaged in the processes outlined in ...